Influence of Teaching Methodologies on Writing and Reading Abilities in Selected Primary Schools of Bubiita Sub-county, Bududa District - Namutosi Mirriam (Uganda Christian University, 2024)
This study examined the influence of teaching methodologies on writing and reading in selected primary schools of Bubiita Sub-County, Bududa District. Teaching methodologies are considered the independent variable, while writing and reading the dependent variable. The purpose of the study was to examine the influence of teaching methodologies on writing and reading ability in selected primary schools in Bubiita Sub-County, Bududa District. The study will be guided by three research objectives which include; i) to examine how Learners-focused teaching methodologies that influence writing and reading ability among learners in selected government aided primary schools in Bubiita Sub-County, ii) to find out the extent to which teaching methodologies influence writing and reading ability among the learners in selected government aided primary schools in Bubiita Sub-County and iii) to establish the extent to which Engagement methodologies influence writing and reading ability among the learners in selected government aided primary schools in Bubiita Sub-County. The study used a cross-sectional research design with both qualitative and quantitative approaches, and data was collected from 260 respondents. Quantitative data was analyzed using SPSS computer software (Version 20) to generate frequencies, percentages. Qualitative data was generated through interviews. Findings of the study revealed that teaching methodologies had statistically insignificant influence on writing and reading ability and this was proposed by 51% of respondents who said that teaching methodologies do not influence writing and reading ability among primary learners in primary schools in Bubiita sub-county. The study recommended that the Ministry of Education, Sports, Science and Technology to have a working policy to foster literacy development in lower primary for teachers in public primary schools since it’s one of the requirements for all school going children. Government could study this teachers’ initiative with a view of improving and supporting the skills. The study also recommended that to improve on the writing and reading ability, it is recommended that education policy makers and implementers establish relevant teaching materials to trigger children’s ability in writing.